Incentives and workers' motivation in the public sector - Josse Delfgaauw; Robert Dur (Center for Economic Studies and ifo Institute (CESifo), 2004)
Civil servants have a bad reputation of being lazy. However, citizens' personal experiences with civil servants appear to be significantly better. We develop a model of an economy in which workers differ in laziness and in public service motivation, and characterise optimal incentive contracts for public sector workers under different informational assumptions. When civil servants' effort is unverifiable, lazy workers find working in the public sector highly attractive and may crowd out workers with a public service motivation. When effort is verifiable, the government optimally attracts motivated workers as well as the economy's laziest workers by offering separating contracts, which are both distorted. Even though contract distortions reduce aggregate welfare, a majority of society may be better off as public goods come at a lower cost.
Keywords: J3; H1; L3; J4; M5; 330; public sector labour markets; incentive contracts; work ethics; public service motivation; Öffentlicher Dienst; Leistungsanreiz; Anreizvertrag; Leistungsmotivation; Arbeitsethik; Theorie; Niederlande